CHARACTERISTICS OF POPULATION HIU PAUS (Rhincodon typus) AND PATTERN OF BEHAVIOR STAY AT THE BEACH BOTUBARANI, BONE BOLANGO, GORONTALO - Kris Handoko; R. Andry Indryasworo Sukmoputro; Mahardika R. Himawan; Casandra Tania (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The purpose of this study is to determine the number of whale sharks that come or appear in Botubarani waters during the year of 2016 - 2017 and monitor the pattern of their live behavior in the amount of days. The monitoring methods used are by (1) using photo IDs to distinguish individual types of whale sharks, (2) monitoring by looking directly / visually and recording the occurrence of whale sharks written in the seasonal calendar system and (3) using acoustic-based technology, by installing 2 (two) units of acoustic receivers at a depth of 15 meters and installing 10 (ten) acoustic signal-transmitting markers on the Whale Sharks. The study was conducted in November 2016, May and November 2017. The number of individuals of whale shark that have been identified is 21 individuals of Whale Shark in total. While the live behavior patterns of Whale Sharks who are installed with acoustic transmitter tag says that whale shark measuring more than 3.5 meters come and stay for about 10 days in the waters of Botubarani. While the Whale Sharks less than 3.5 meters in size stay for about 1 - 7 days. The results of direct whale monitoring (visual) of the pattern of live behavior of Whale Shark in the number of days of emergence during the period November 2016 to November 2017 from the data obtained are: 17 days in November 2016, 2 days in January 2017, 14 day in February 2017, 8 days in March 2017, 28 days in May 2017, 21 days in June 2017 and 2 days in July. While Whale Sharks did not appear in Botubarani in December 2016, April 2017, August 2017, September 2017, October 2017 and November 2017. Keywords Whale Sharks, Photo IDs, Acoustic Bookmarks